The role of predatory nematodes in managing plant-parasitic nematodes: community dynamics and microbial implications in tropical soils - Singh, Richard Raj; Iyekar, Clancy (Frontiers in Plant Science, 2025)
Plant-parasitic nematodes (PPNs) pose a significant threat to banana cultivation, particularly in tropical regions like Guam. This study investigates the dynamics of nematode communities associated with banana cultivars, focusing on interactions between predatory nematodes (Mononchus spp.) and PPNs (Meloidogyne spp.), and their implications for soil health. Our aim was to evaluate the response of cultivars to nematode prevalence while characterizing nematode community structure and soil chemical properties. Soil and root samples were assessed for nematode communities. Controlled pot experiments were also performed in tomatoes to evaluate predator-prey interactions. The results showed no differences in nematode densities among the banana cultivars, indicating uniform susceptibility to PPNs. We identified three predominant PPN genera: Meloidogyne (root-knot nematodes), Helicotylenchus (spiral nematodes), and Pratylenchus (lesion nematodes), with Meloidogyne as the most dominant. Soil samples contained a higher abundance of bacterivores and predatory nematodes when compared to PPNs. Furthermore, soil analysis revealed high organic matter content and elevated carbon and nitrogen levels. Our temporal analysis revealed that the interaction strength between predatory nematodes and plant-parasitic nematodes (PPNs) increased over time, resulting in a significant reduction in gall formation, egg-laying females, and juvenile populations in tomatoes. This relationship was further quantified through interaction strength (I) values derived from the soil analysis of predatory and root-knot nematodes. In conclusion, our findings highlight the potential for integrating predatory nematodes into pest management. By emphasizing the balance between beneficial nematodes and PPNs, this study provides novel insights applicable to sustainable agricultural practices.